Jewish ethnic identity and relations in Hellenistic Egypt: with walls of iron? - Moore, Stewart Alden (Journal for the study of Judaism, 2015)
Front Matter -- Introduction -- Thicker than Water? A Social-Scientific Approach to Ancient Judean Ethnicity -- The History of Dustbins: Reconstructing Ethnicity from the Papyri -- Reflections on the Nile: Greek Ethnographers and the Egyptians’ Boundary -- From the Mouths of Beasts: Ethnic Identity in Apocalyptic Literature from Egypt -- For the Sake of Mice and Weasels: Ethnic Boundaries and the “Cultural Stuff” in the Letter of Aristeas -- Conclusion -- Bibliography -- Subject Index.